Smart cities and communities in the GCC region: from top-down city development to more local approaches - Al-Saidi, Mohammad; Zaidan, Esmat (Frontiers in Built Environment, 2024)
City planners are seeking ways to incorporate human-centric urban projects that combine smart technology, good infrastructure and people's perception as well as their participation. Smart city developments are increasingly being applied to smaller scales at which communities can co-design hard infrastructure and the resulting services. Experiences from city projects at this level have produced a plethora of designs, challenges and success factors, particularly from cases in countries with long legacies in city development. In the Gulf Cooperation Council (GCC) region, young cities and new planned cities house the bulk of the population of the Gulf countries and face environmental challenges related to, urban segregation, urban sprawl and large consumption footprints. This political-economy of this region in terms of central urban planning and government-led economic development offers valuable insights on the limits and challenges in implementing projects related smart and connected communities (SCC). SCC as label for smart urban interventions towards more connectedness between hard and soft (human-related) infrastructure can provides opportunities for participatory and sustainable urban planning in the region. This paper analyzes the role of community-level interventions within the smart city policies of Gulf countries. It shows that only few local-level projects exist, while the barriers to large-scale SCC initiatives are related to demographics, community characteristics, technological sophistication, lack of conducive regulations, and the prevalence of central urban planning. The success of local smart city approaches in the Gulf is dependent on public leadership in terms of clearing obstacles, designing broader strategies, and expanding projects to include the residential sector. By considering the potential for community engagement to enhance the transition to sustainability in the predominantly urban Gulf societies, broader engagement of local governments, utilities, and community-level developers can result in tangible benefits in terms of more sustainable, smart and tailored local services.